Clinical Pharmacological Approach To The Use Of Hypolipidemic Drugs In The Treatment Of Atherosclerotic Disease (Texas Journal of Medical Science, 2025)
To evaluate the hypolipidemic effect, the impact on endothelial function, oxidative stress of pitavastatin at a dose of 4 mg in patients with dyslipidemia, arterial hypertension (AH) and chronic obstructive pulmonary disease (COPD) at baseline, in dynamics after 4 weeks and 12 months of treatment. The prospective study included 33 patients (mean age – 60 years) with hypertension, COPD and dyslipidemia. Laboratory examination consisted of determining the lipid spectrum, the level of lipid peroxidation products (LPO). In order to assess the tolerability of the prescribed therapy, creatinine, bilirubin, alanine aminotransferase (ALT), aspartate aminotransferase (AST) were studied